Detection of biogenic amines in urine and plasma by liquid chromatography coupled to electrochemical detection HPLC-ED using microextraction in packed syringe MEPS - Oppolzer, David Jerónimo (2012)
Biogenic amines are neurotransmitters involved in several physiological processes. Changes and disturbs in their function are associated to several neurological disorders or diseases, as well as consumption of psychotherapeutic or psychotropic drugs. The detection of these compounds in biological fluids is therefore of clinical and neurochemical interest. The goal of this work was to develop and validate and analytical method for the detection and quantification of the biogenic amines serotonin (5-HT), dopamine (DA) and norepinephrine (NE), using microextraction in packed syringe (MEPS) and liquid chromatography coupled to electrochemical detection (HPLC-ED) in both urine and plasma samples. The internal standard used was 3,4-dihydroxybenzylamine (DHBA). The MEPS extraction procedure was optimized using the design of experiments (DOE) tool, and the final conditions of 8 strokes, no washing, and two elutions of 100 FL methanol were chosen. The method was fully validated according to internationally accepted guidelines from the Food and Drug Administration. Linearity was established between 50-1000 ng/mL for 5-HT and between 5-1000 ng/mL for DA and NE, with determination coefficients (R2) higher than 0.99 for all compounds. The limits of detection and quantification were respectively 20 and 50 ng/mL for 5-HT, and 2 and 5 ng/mL for DA and NE. Intra- and interday precision ranged from 1 to 10 %, while accuracy was within a ±15% interval for all compounds. Authentic urine and plasma samples were analysed by the validated method, and the three compounds were detectable and quantifiable in urine, while only 5-HT was detected and quantified in plasma. This is the first time that a commercially available MEPS column was used for the simultaneous detection of biogenic amines in urine, and also the first time that 5-HT was detected and quantified in plasma using MEPS. MEPS proved to be fast to perform with the use of less solvent volumes, saving time and money and being less laborious. The validated method is useful for the determination of biogenic amines in laboratorial routine.